Evaluation of Neck Vessel Injury in Patients with Blunt Trauma to the Cervical Spine - Kumar G, Krishna; Singla, Navneet; Gupta, Vivek; Gupta, Sunil Kumar (Indian Journal of Neurotrauma, 2015)
Injuries to the neck vessels often go undiagnosed in patients with cervical spinal trauma. In this prospective study, 50 patients of cervical spine injury who were hemodynamically stable were evaluated by CT angiogram for presence or absence of carotid and/or vertebral artery injury. Three (6%) patients were diagnosed to have vertebral artery injury. None of the patients had a carotid artery injury. The clinical presentation and management protocol are discussed.
Keywords: cervical spine trauma; vertebral artery injury